PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BATIK PADA IMAH BATIK SAHATE DI RANGKASBITUNG - Muhammad Abdul Khosyi; Eris Harismasakti (Universitas La Tansa Mashiro, 2025)
January to June 12 2024, the sales volume decreased every month. In January, the sales volume reached 236 batik cloth with a production volume of 324 batik cloth and leaving 88 products unsold, so in February only produced 264 batik cloth and sold 108 batik cloth. Then the price of raw materials experienced increases and decreases, such as in January the price of raw materials with a total production of 4103 batik cloths cost IDR 7,010,000, then in February it cost IDR 3,010,000. This research used a sampling technique, namely random sampling using the Slovin formula, as many as 67 people/employees. The data analysis method used is descriptive and hypothesis testing uses regression analysis with the SPSS 25.00 for Windows program. There is a significant influence of price (X1) on purchasing decisions (Y). There is a significant influence of product quality (X2) on purchasing decisions (Y). There is a significant influence of Price (X1) and Product Quality (X2) which together (simultaneously) have a significant influence on purchasing decisions (Y).